Compromiser - a notional paradigm - Paradis, Carita (HERMES - Journal of Language and Communication in Business, 2017)
On the basis of an investigation of the lexical forms quite, rather, fairly, and pretty in contemporary spoken British English, I postulate that these lexical items form a notional paradigm of compromiser within the category of degree modifiers. Compromisers are cognitive synonyms that occupy the middle of an abstract intensity scale, approximating a mean degree of another word, eg quite / rather / fairly / pretty dirty. They are all polysemous and poly-functional words, whose meanings are determined by a crucial semantic trait ‘to a moderate degree’ on the paradigmatic axis, and by a semantic-syntactic, selection-licensing mechanism on the syntagmatic axis.